PERSPEKTIF PENINGKATAN PRODUKSI PADI DI KABUPATEN LAMONGAN - Alviyah Yunianti; Elys Fauziyah (Universitas Sebelas Maret, 2015)
The aim of this research are to know the result of rice product forecasting at Lamongan regency in 2016 and identify the factor influence rice production. This research was done at Lamongan by using cluster method. The total number of respondents are 60 farmers. Data were analyzed with ARIMA and multiple regression method. The results show that the rice production forecasting at Lamongan in 2016 will increas approximately 1.022.488 ton, and the factors influence rice production are land area, urea, labor and capital. If each those variables are increased, it will be able to increase the result of rice production.